Microsoft Azure Administrator (AZ-104) - Gordon, Adam (Packt Publishing, 2024)
In this course, you'll start with an overview of managing Azure AD objects, understanding the significance of each task. You will learn how to create and manage users and groups, ensuring proper access and permissions within your organization. Dive into the management of licenses, a crucial aspect for cost-effective use of Azure AD, and explore the creation of administrative units to delegate administrative tasks efficiently. Next, the course will guide you through managing user and group properties, and configuring device settings and device identity, essential for maintaining security and compliance. You will also master bulk updates, streamlining processes that involve multiple users or groups. The course then focuses on managing guest accounts, a critical feature for collaborating with external partners securely. Finally, you will learn to configure self-service password reset, empowering users to manage their passwords without administrative intervention, reducing support costs and improving user satisfaction. Each section is designed to build your confidence and competence in managing Azure AD, equipping you with the skills needed to maintain a secure and efficient digital environment.